2021
DOI: 10.1093/eurheartj/ehab316
|View full text |Cite
|
Sign up to set email alerts
|

DUSP26 induces aortic valve calcification by antagonizing MDM2-mediated ubiquitination of DPP4 in human valvular interstitial cells

Abstract: Aims  The morbidity and mortality rates of calcific aortic valve disease (CAVD) remain high while treatment options are limited. Here, we evaluated the role and therapeutic value of dual-specificity phosphatase 26 (DUSP26) in CAVD. Methods and results  Microarray profiling of human calcific aortic valves and normal controls demonstrated that DUSP26 was significantly up-regulated in calcific aortic valves. ApoE−/− mice fed a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Genome-wide association study (GWAS), however, have revealed a single nucleotide polymorphism with a strong independent predictive association with the development of AS; and multi-omics study has identified potential effector proteins and expressed genes linking Lp(a) to valvular calcification ( 206 , 207 ). Wang et al utilised multi-omic screening of explanted human aortic valve specimens to identify dual-specificity phosphatase 26 (DUSP26) as an upregulated gene promoting aortic valve calcification in CAVD, subsequently using in vivo mouse and in vitro human VIC studies to confirm that DUSP26 promotes CAVD via upregulation of dipeptidyl peptidase 4 (DPP4) ( 208 ). Moving forward, multi-omics studies have great potential to identify genes, proteins and small molecules that may be targetted in medical treatment for CAVD.…”
Section: Working Toward Uncoupling the Vicious Cycle Of Inflammation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Genome-wide association study (GWAS), however, have revealed a single nucleotide polymorphism with a strong independent predictive association with the development of AS; and multi-omics study has identified potential effector proteins and expressed genes linking Lp(a) to valvular calcification ( 206 , 207 ). Wang et al utilised multi-omic screening of explanted human aortic valve specimens to identify dual-specificity phosphatase 26 (DUSP26) as an upregulated gene promoting aortic valve calcification in CAVD, subsequently using in vivo mouse and in vitro human VIC studies to confirm that DUSP26 promotes CAVD via upregulation of dipeptidyl peptidase 4 (DPP4) ( 208 ). Moving forward, multi-omics studies have great potential to identify genes, proteins and small molecules that may be targetted in medical treatment for CAVD.…”
Section: Working Toward Uncoupling the Vicious Cycle Of Inflammation ...mentioning
confidence: 99%
“…In addition to identifying new molecular targets, existing therapeutic agents may be repurposed in the treatment of CAVD ( 209 ). As mechanistic studies identify new mediators of CAVD, existing drugs such as DPP4 inhibitors currently used in the treatment of diabetes may become candidates for the treatment of CAVD ( 208 ). Similarly, proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have shown efficacy in the treatment of coronary artery disease, and upregulation of PCSK9 has been identified in human CAVD and promotes VIC calcification in vitro ( 210 ).…”
Section: Working Toward Uncoupling the Vicious Cycle Of Inflammation ...mentioning
confidence: 99%
“…However, the molecular mechanism that determines the target specificity of these enzymes is far from being elucidated, and too often the exact dephosphorylated residue is unknown, as is the phosphatase region that allows for the recognition. This knowledge is crucial for any clinical application, in order not to mislead the models, particularly for Dusp26 that has been recently associated with different pathologies such as cancer, as well as metabolic and neurodegenerative disorders [49,50]. Despite the fact that Dusp26, as many other phosphatases, has been considered an "undruggable" target, three chemical inhibitors of Dusp26 have been reported in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional expression of ubiquitin E3 ligases, which mainly determines the specificity and rate-limiting step of ubiquitination, plays an essential role in the pathological processes of various diseases [ 8 , 9 ]. Regulating the levels of ubiquitin E3 ligases has been proven to be able to treat many cardiovascular diseases, such as cardiac hypertrophy, valve calcification, and pulmonary arterial hypertension [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%